Is a Special Environmental Court Necessary for Civil Lawsuits in Indonesia? A Comparative Study of Judicial Decisions in New Zealand and Hawaii - Trias hernanda; Nur Aida Ikrima; Sunardi Sunardi (Jurnal Jurisprudence, 2025)
ABSTRACT Purpose of the Study: This research aims to analyze the urgency in forming a special environmental court in Indonesia by analyzing judges’ legal decisions in the case of civil liability over environmental destruction. This analysis also compares the legal system in Indonesia with environmental justice models in New Zealand and Hawaii to find the best practices in enforcing environmental justice. Methodology: The method used was the normative legal research with a legal comparison approach. The data used were in the form of secondary data obtained through literary studies, which were qualitatively analyzed through legal reasoning and the comparison of interstate justice systems. Results: Research results showed that the general court system in Indonesia is still ineffective in handling environmental cases due to the lack of judges’ technical understanding and the lack of a special justice institution handling environmental cases. Meanwhile, New Zealand and Hawaii have shown the effectiveness of their environmental justice systems through the strengthening of technical aspects, institutional independence, and the consistent application of civil liability.                                                                                               Applications of this Study: This research is beneficial as a recommendation to renew the Indonesian justice system to achieve a more responsive environmental justice system. Novelty/Originality of this Study: This research’s novelty is placed on the analysis of the relationship between judges’ legal considerations and the urgency in forming an environmental justice system based on interstate comparison. Keywords: Civil Responsibility, Environmental Justice, Hawaii, Indonesia, New Zealand.   ABSTRAK Tujuan Penelitian: Penelitian ini bertujuan untuk menganalisis urgensi pembentukan peradilan khusus lingkungan hidup di Indonesia dengan meninjau pertimbangan hukum hakim dalam perkara pertanggungjawaban perdata atas kerusakan lingkungan. Kajian ini juga membandingkan sistem hukum Indonesia dengan model peradilan lingkungan di Selandia Baru dan Hawaii untuk menemukan praktik terbaik dalam penegakan keadilan lingkungan. Metode: Metode yang digunakan adalah penelitian hukum normatif dengan pendekatan perbandingan hukum. Data yang digunakan berupa data sekunder yang diperoleh melalui studi kepustakaan yang dianalisis secara kualitatif melalui penalaran hukum dan perbandingan sistem peradilan antarnegara. Hasil penelitian: Hasil penelitian menunjukkan bahwa sistem peradilan umum di Indonesia masih belum efektif dalam menangani perkara lingkungan karena kurangnya pemahaman teknis hakim dan belum adanya lembaga peradilan yang khusus menangani kasus lingkungan. Sebaliknya, Selandia Baru dan Hawaii telah menunjukkan efektivitas peradilan lingkungan melalui penguatan aspek teknis, independensi kelembagaan, dan penerapan pertanggungjawaban perdata yang konsisten. Penerapan Penelitian: Penelitian ini bermanfaat sebagai rekomendasi pembaruan sistem peradilan di Indonesia menuju keadilan lingkungan yang lebih responsif. Kebaruan/Orisinalitas: Kebaruan penelitian ini terletak pada analisis hubungan antara pertimbangan hukum hakim dan urgensi pembentukan peradilan lingkungan hidup berdasarkan perbandingan lintas negara. Kata Kunci: Pertanggungjawaban Perdata, Peradilan Lingkungan, Hawaii, Selandia Baru, Indonesia